2017
DOI: 10.1542/peds.2017-1818
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabinoids in Children and Adolescents: A Systematic Review

Abstract: Additional research is needed to evaluate the potential role of medical cannabinoids in children and adolescents, especially given increasing accessibility from state legalization and potential psychiatric and neurocognitive adverse effects identified from studies of recreational cannabis use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 60 publications
5
89
0
14
Order By: Relevance
“…In this case study, both the family’s report as well as the expert clinical ratings suggested that not only THC – as described earlier [8] – but also vaporized cannabis are effective in the reduction of tics and premonitory urges. Remarkably, even relatively high doses of THC were well tolerated and even improved concentration according to the patient’s report.…”
Section: Discussion/conclusionsupporting
confidence: 60%
See 2 more Smart Citations
“…In this case study, both the family’s report as well as the expert clinical ratings suggested that not only THC – as described earlier [8] – but also vaporized cannabis are effective in the reduction of tics and premonitory urges. Remarkably, even relatively high doses of THC were well tolerated and even improved concentration according to the patient’s report.…”
Section: Discussion/conclusionsupporting
confidence: 60%
“…While there is increasing evidence that CBM is effective in the treatment of a variety of conditions in adult populations [7], only very little is known about efficacy and safety of CBM in children and adolescents [8]. In a recent systematic review, only 22 studies have been identified using CBM in minors, most commonly pure THC and cannabidiol [8].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonhematological adverse events recorded during each study chemotherapy block were described and graded based on the Common Terminology Criteria for Adverse Events (CTCAE) Version 4.03 . Particular attention was paid to identify drowsiness, dizziness, and euphoria since they have been previously reported to be associated with nabilone . All adverse events noted in patient charts that were attributed to nabilone by health care providers were included.…”
Section: Introductionmentioning
confidence: 99%
“…Some parents report that they give cannabis products to their children to help with their behaviour and increasingly, Australian parents of children with developmental disabilities and/or mental health disorders are asking their paediatricians if MC treatment is advisable and whether they can assist them in obtaining it for their child. The American Academy of Pediatrics has highlighted the need for further research into the therapeutic uses of cannabinoids in children and adolescents, a position supported by a recent systematic review …”
mentioning
confidence: 99%